Records management system of the Police Regional Office I : an assesstment - Gavina, Mayla Perla G. (Dagupan City : [s.n.], 2018)
This study assessed and analyzed the present records management system of the Police Regional Office 1 at San Fernando City, La Union with the end view of making improvements thereto. Descriptive method was used in this research to assess the present records management system of the Police Regional Office 1 in order to recommend measures to improve present system. Survey questionnaire was constructed and was distributed to selected personnel of PRO1. This study involved the total population of the 24 police personnel from the different offices of the Police Regional Office 1 who are directly involved in handling the records of the Philippine National Police.
Bibliography: page 65.
CHED-La Union
Keywords: Records -- Management